Organisms, Resistance and Outcomes in Septic Shock Patients Admitted to a Saudi Intensive Care Unit - Haifa Algethamy; Nora M. Althubaiti (Journal of King Abdulaziz University: Medical Sciences, 2021)
In this prospective study within a Saudi Arabian hospital, culture and sensitivity results and their impact upon outcomes were assessed in adult patients with septic shock admitted to our intensive care unit and followed for at least 30 days, or until hospital discharge or death. One hundred and sixty one (161) adult patients with septic shock were included in the study. The mean age was 61.6 y and male to female ratio was 1. The most common organisms cultured were Escherichia coli (in 26.1% of patients), Klebsiella pneumoniae (18.6%), Pseudomonas aeruginosa (17.4%) and Staphylococcus aureus (16.1%). Antibiotic resistance was observed in 62%, 30%, 7% and 50%, of these organisms, respectively. The mortality rates were 46%, 55%, 36% and 65%, respectively. Thirty-three percent of patients had two to four bacteria cultured. On multivariable analysis, predictors of in-hospital mortality were negative cultures, high Sepsis-related Organ Failure Assessment (SOFA) score on ICU day 11, and increase in SOFA score on day 3. Factors predictive of more major complications were high day 1 SOFA score, a history of diabetic complications, and increase in the SOFA score on day 3, whereas, factors predictive of less complications were a history of kidney disease and being culture positive for either Streptococcus or Klebsiella.